2014
DOI: 10.1253/circj.cj-14-0670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Statin Loading on Biomarkers Related to Inflammation and Renal Injury in Patients Hospitalized With Acute Heart Failure

Abstract: Background: High-dose statin loading is known to reduce periprocedural myocardial infarction and contrast-induced acute kidney injury in patients undergoing percutaneous coronary intervention. However, the clinical role of high-dose statin loading in patients with acute heart failure (AHF) remains unknown. Methods and Results:In a prospective, single-center, randomized, controlled, open-label pilot study, patients hospitalized with AHF were randomly assigned to receive oral high-dose atorvastatin loading (80 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…10 Statin therapy for CHF was considered controversial in other studies. 11,12 In our study, no benefit was observed in both statin cohorts and both sexes. A 2-year comparison of hydrophilic and lipophilic statin studies showed no significant difference in AMI.…”
Section: Hydrophilic or Lipophilic Statins For Cardiovascular Eventscontrasting
confidence: 62%
“…10 Statin therapy for CHF was considered controversial in other studies. 11,12 In our study, no benefit was observed in both statin cohorts and both sexes. A 2-year comparison of hydrophilic and lipophilic statin studies showed no significant difference in AMI.…”
Section: Hydrophilic or Lipophilic Statins For Cardiovascular Eventscontrasting
confidence: 62%
“…Due to inconclusive results from prior investigations, there is still controversy regarding the statements. [3][4][5][6][7][8] The relationship between the risk of cardiovascular outcomes and DM is well-known. Despite higher incidence of associated higher morbidity and mortality, venous thromboembolism (VTE) attracts less attention compared to other adverse outcomes among DM subjects.…”
Section: Introductionmentioning
confidence: 99%
“…35 Furthermore, compared to Cr, present biomarkers reflect the renal dysfunction rapidly and may be more suitable for clinical trials that focus on acute-illness patients. 36 Neutrophil gelatinase-associated lipocalin is a 25-kDa protein of the lipocalin family that is produced by neutrophil and also expressed in the kidney, liver, and epithelial cells during acute pathologic states such as inflammation, infection, intoxication, ischemia, and neoplastic transformation. 37 In AKI, both upregulated NGAL expression in the distal nephron and impaired proximal tubular NGAL reabsorption contribute to increased urinary and plasma NGAL levels.…”
Section: Resultsmentioning
confidence: 99%